A biomineralized Prussian blue nanotherapeutic for enhanced cancer photothermal therapy. Issue 25 (14th June 2022) - Zhong, Daliang; Wang, Yuxin; Xie, Fan; Chen, Siying; Yang, Xinyan; Ma, Zaiqiang; Wang, Shibo; Iqbal, M. Zubair; Ge, Jian; Zhang, Quan; Zhao, Ruibo; Kong, Xiangdong
Abstract : Biomineralization has been introduced to improve the photothermal conversion efficiency of Prussian blue, representing a novel strategy for Prussian blue-based cancer photothermal therapy. Abstract : Photothermal therapy is a promising tumor ablation technique that converts light into heat energy to kill cancer cells. Prussian blue (PB), a biocompatible photothermal reagent, has been widely explored for cancer treatment. However, the translational potential of PB is severely hampered by its low photothermal conversion efficiency (PCE) and poor stability. To tackle these issues, we adopted the biomineralization modality where PB was integrated with calcium phosphate (CaP) through the binding between calcium ions and PB. The mineralized PB (CaP&PB) demonstrated significantly improved PCE (40.2%), resulting from a calcium-induced bandgap-narrowing effect, and exhibited superior suspension stability. Using a 4T1 orthotopic breast cancer BALB/c mouse model, we observed that mineralized PB showed a significant temperature increase within the tumor, which led to better tumoricidal activity compared with CaP and PB when identical NIR treatment was applied. These achievements demonstrated the success of introducing calcium phosphate into Prussian blue by biomineralization to improve the PCE and stability of photothermal reagents, suggesting an alternative translational strategy for enhanced cancer photothermal therapy.